India's Image as a destination for British tourists - Agrawal, Tanvi (2007)
Destination image is a popular topic in tourism research due to its high ended importance in understanding the destination selection process. It is an important concept which helps in assessing the perceptions of target market tourist. A destination can realize its full tourism potential only once it has a favourable image and thus Destination marketers are on a constant move towards creating a positive image through various marketing strategies and destination positioning. India is a soaring economy with a huge potential for tourism. The UK is one of the most important tourism generating countries for India. The destination managers of India are striving towards tapping these key tourism generating markets. With respect to destination image very few studies have focused specifically on India and none of them have analyzed the Image of India as a destination for British tourist. Thus the aim of this study was to rectify this knowledge deficit. The use of both qualitative and quantitative methods of interviews and survey in this study revealed the fact that the overall Image of India as perceived by the British is positive, varying across various tourism sub-sectors with respect to both British visitors and non- visitors. From a practical viewpoint this research helped in identifying the destination positioning and marketing strategies to be undertaken by the Indian tourism authorities.